PENGARUH DIKLAT DAN KOMPETENSI ASN TERHADAP KINERJA ASN MELALUI DISIPLIN KERJA SEBAGAI VARIABEL INTERVENING PADA DINAS PERTANIAN DAN KETAHANAN PANGAN KABUPATEN BONDOWOSO - Kholis, Nur; Kusnadi, Edy; Fandiyanto, Randika (Fakultas Ekonomi dan Bisnis, 2022)
Human resource management is a field of management that specializes in studying the relationship and role of humans in organizations, facing the current of globalization, human resources are very dominant in playing a role in organizational activities and activities, human resources are also seen as the most valuable asset and have a very important role. In the survival of the organization, the purpose of this study is to analyze and test, the effect of ASN Training and Competence on ASN Performance through ASN Work Discipline as an Intervening Variable at the Department of Agriculture and Food Security in Bondowoso Regency. Bondowoso district. The sampling method was determined by non-probability sampling. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that Education and Training has a significant effect on work discipline, Competence has a negative but not significant effect on work discipline, Education and training has a negative but not significant effect on ASN Performance, Competence has a significant positive but not significant effect on ASN Performance, Work discipline has a significant positive effect on the performance of ASN. The results of the indirect effect hypothesis test show that Training and Education on ASN Performance, through work discipline, has a significant positive effect, Competence on ASN Performance through work discipline has a negative but not significant effect.